Catch 22 of Common Man’s Masculinity in Arthur Miller’s Death of a Salesman - Nepali, Mukta Bahadur (Tribhuvan Journal, 2023)
Arthur Miller’s “Death of a Salesman” (1949) presents the working-class masculinity under threat. This paper has sought to argue that the threat is posed not only by the protagonist’s inability to assert his working-class masculine identity due to his (fear of) unemployment, but also by the instrumental use of reason by the employer and hegemonic masculinity. It has tried to unfold this threat in terms of R. Connell’s idea of ‘hegemonic masculinity’ and CALM report on crisis of modern masculinity published in 2014. The assumption is that Miller has depicted this threat by presenting the male protagonist in such an unfavorable situation that it relegates him to the vulnerable position of not being able to assert his masculine identity. It is also assumed that this threat is further validated by the presence of dominant masculinity. This research has sought to dramatize the playwright's consciousness of the masculinities in conflict and its outcome in America. This research is critically significant because reading this drama from the perspective of the crisis of subordinate or working-class masculinity is a far cry.